PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT POS INDONESIA JAKARTA SELATAN - Muhammad Daffa Muzhaffar; Ibrahim Bali Pamungkas (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of leadership style and compensation on employee performance at PT Pos Indonesia, South Jakarta. This research uses quantitative methods. The sampling technique is using a saturated sample with a population of 65 employees, so that the sample used is the total number of populations that can be accepted in research. The data collection technique in this research uses questionnaires. The analysis method uses instrument testing, assumption testing. classical, regression testing, correlation coefficient testing and coefficient of determination and hypothesis testing . The research results show that Leadership Style (X1) has a significant effect on Employee Performance (Y) by showing the test results t = 15.506 while t table = 1,99834 (t count < t table ) with a significance level of 0.000 < 0.05, so H0 is rejected and H1 is accepted. t test results The research variable Compensation (X2) has a significant effect on Employee Performance (Y) by showing the results of the t test = 15.876 while t table = 1,99834 (tcount > ttable) with a significance level of 0.000 < 0.05, then H2 is accepted and H0 is rejected. Based on the results of the Anova test, the Fcount value was 197.531 which was greater than Ftable with a significant 0.000 smaller than 0.05 (Fsignificant 0.000 < 0.05). So it can be concluded that simultaneously Leadership Style (X1) and Compensation (X2) together have a significant effect on Employee Performance (Y). With this data it is known that there is an influence of Leadership Style and Compensation on Employee Performance at PT. Pos Indonesia South Jakarta.